Child-centered play therapy research : the evidence base for effective practice - Baggerly, Jennifer; Bratton, Sue; Ray, Dee C. (Wiley Online Library., 2010)
The first book of its kind to provide exhaustive, in-depth coverage of play therapy research. Child-Centered Play Therapy Research: The Evidence Base for Effective Practice offers mental health professionals, school district administrators, community agency administrators, judges, lawyers, child protection caseworkers, and medical professionals a comprehensive discussion of play therapy research studies. Guidance is provided on evidence-based methods, as well as on how¿future play therapy research should be conducted. Edited by renowned experts in the field of play therapy, this rich compilation features contributions by child-centered play therapy researchers, with relevant discussion of: * The history of play therapy research * A synopsis of current empirical support * Play therapy research on chronically ill children, child witnesses of domestic violence, and victims of natural disasters, among many other topics With coverage of important practice guidelines, Child-Centered Play Therapy Research identifies the most prominent and current play therapy research studies, as well as research directions for clinicians to design evidence-based research studies of their own.